ANALISIS FUNGSI PENGAWASAN DINAS PERHUBUNGAN TERHADAP PENGELOLAAN PARKIR TEPI JALAN UMUM DI KOTA PEKANBARU TAHUN 2022 - ASANO, ADISTY; Yusri, Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Supervision of parking activities is carried out by the UPT.Parkiran Transportation Service in accordance with Mayor Regulation Number 284 of 2017. The large number of parking locations in Pekanbaru City requires UPT.Parkiran to carry out optimal supervision. However, the phenomenon in the field is that there are still many problems regarding parking such as illegal parking and illegal parking attendants. Based on this phenomenon, the aim of this research is to determine the implementation of the Transportation Department's supervisory function regarding the management of public roadside parking in Pekanbaru City in 2022, and to determine the inhibiting factors in the implementation of this supervisory function. This research is a type of descriptive research using a qualitative approach that describes phenomena in words rather than numbers. Data collection techniques in this research used interview and documentation techniques with the Purposive Sampling model in selecting samples. Data analysis uses the Miles and Huberman model with 3 stages, namely data reduction, data presentation, and drawing conclusions. The theory in this research uses Supervision theory according to Kadarman Udayana, namely setting standards, measuring performance and analyzing deviations. And according to Muchsan, the theory that hinders supervision is that the seriousness or quality of the performance of the officers is not good. The findings that can be concluded from the Analysis of the Supervision Function of the Transportation Service regarding the Management of Public Roadside Parking in Pekanbaru City in 2022 which is based on the theory used is supervision carried out by the UPT. Parking takes the form of routine patrols to several places every day by checking parking locations and attendants. parking on duty. However, this supervision has not been running optimally as seen from the large number of illegal parking on the side of public roads such as in the Arifin Achmad Regional Hospital and SKA Mall area, as well as parking attendants who work not according to standards. Obstacles found in the monitoring process include the seriousness of the UPT's performance. Parking is found in human resources who are less competent and firm in giving sanctions to violators, less responsive to input from the public, and less informative regarding enforcement raids and where the official parking locations are. Keywords: Supervision, Government, Parking management